PERAN INDUSTRI HALAL DALAM MENGDONGKRAK PERTUMBUHAN EKONOMI INDONESIA DI ERA NEW NORMAL - Evita Farcha Kamila (Prodi Ekonomi Syariah Fakultas Ekonomi dan Bisnis Islam UIN Sunan Gunung Djati Bandung, 2021)
The Covid 19 disaster that the WHO (World Health Organization) has designated as a pandemic is not just a health problem, far from it covers all aspects that also weaken economic conditions. China, as a country that is the epicenter of the first spread of this virus which incidentally is the country with the second largest economy in the world, of course greatly affects the pace of the global economy. Some of the world's credible research institutes also predict the bad impact of this outbreak on the global economic pace. Including Indonesia, the finance minister, Sri Mulyani Indrawati also predicted the impact on the economy with the worst case scenario could reach minus 0.4%. Among the forms of efforts being called for and carried out by the world to reduce the spread of this epidemic is social distancing, in Indonesia, physical distancing is more enforced. But unfortunately, this movement resulted in a decline in overall economic activity. This effort is good on the one hand but also results in a decrease in Aggregate Supply supply and Aggregate Demand due to activity restrictions and just staying at home which also affects the continuous decline in the amount of production. So due to the Covid 19 virus pandemic, it is very large and its potential role can be maximized for the sake of economic progress, especially in Indonesia. Nowadays people really pay attention to health, one of which is consuming and buying products whose hygiene is guaranteed. Then the halal products will take the market position in the new normal era economy. The purpose of writing is to find out how the role of the halal industry in rebuilding the economy in this new normal era. The method used is a descriptive qualitative approach, an effort to understand the various concepts found in the research process, using content analysis techniques and library research. The results showed the projection of the halal industry in the new normal era which has the potential to suit the conditions, opportunities and government efforts in developing the economy in the new normal era. So in this era of new habits, the government, business people, and society can adapt to new economic patterns in order to advance the economy in the new normal era.Keywords: Halal industry, new normal, economy